PENGEMBANGANMODELREMEDI MATEMATIKASMA BERBANTUANKOMPUTER. - Boko Susilo (Jurnal Cakrawala Pendidikan, 2005)
This article is about a research conducted to design and implement the development of a software model for a program of computer-assisted instruction (CAl) used to remedy senior high school students' achievement in learning mathematics (especially in the 1 quarter ofthe school year in the 2'd grade) as well as to determine the effectiveness ofa model'of CAl, the st level ofstudent achievement in learning mathematics after an implementation ofa model ofcomputer-assisted remedial teaching, and such students' opinion on the implementation of a model of computer-assisted teaching of mathematics at senior high school. The data were collected by giving pre tests and post-tests as well as questionnaires to a random sarnple of senior high school students in the city ofBengkulu taken as the population ofthe research. The computer-assisted remedial teaching was designed and programmed by using Authorware®, a computer program for making computer-based teaching materials using the Windows system ofoperation. To gain the research objectives, the data were analyzed by means ofthe t test and argumentative description. The research findings indicate that statistically the model ofcomputer-assisted remedial teaching ofmathematics has been significantly effective and the level ofstudents'learning achievement after the remedial teaching has significantly improved.